BIMBINGAN KONSELING KARIR ISLAM UNTUK MENINGKATKAN KEMATANGAN KARIR MAHASISWA TINGKAT AKHIR - Khairunnisa Syamsu; Hengki Satrianta (Al-Irsyad Al-Nafs : Jurnal Bimbingan dan Penyuluhan Islam)
Career maturity is readiness of individuals to deal with the tasks of their career development. Student’s career maturity can be seen through the readiness of students to work in accordance with their education. This study aims to describe the career maturity of IAIN Kendari students. This was quantitative research with survey type. Population of this study was final-year students of Islamic Guidance and Counseling of IAIN Kendari were amounted to 25 students. This research is a population study so that the entire population becomes the research sample. Data in this study were collected by the scale of career maturity. The results showed that the career maturity level of students was in the low category with a percentage of 24%.